Join IDNLearn.com and become part of a knowledge-sharing community that thrives on curiosity. Discover comprehensive answers from knowledgeable members of our community, covering a wide range of topics to meet all your informational needs.
Sagot :
To solve this system of linear equations using substitution, we follow these steps:
Given:
[tex]\[ \begin{array}{l} x = 3 + y \\ 2x + 8y = -124 \end{array} \][/tex]
1. Substitute the expression for [tex]\(x\)[/tex] from the first equation into the second equation.
The first equation gives us:
[tex]\[ x = 3 + y \][/tex]
Substitute [tex]\(x\)[/tex] in the second equation:
[tex]\[ 2(3 + y) + 8y = -124 \][/tex]
2. Simplify the equation
Distribute the 2 in the equation:
[tex]\[ 6 + 2y + 8y = -124 \][/tex]
Combine like terms:
[tex]\[ 6 + 10y = -124 \][/tex]
3. Isolate the variable [tex]\(y\)[/tex]
Subtract 6 from both sides of the equation:
[tex]\[ 10y = -124 - 6 \][/tex]
Simplify the right-hand side:
[tex]\[ 10y = -130 \][/tex]
Divide both sides by 10:
[tex]\[ y = \frac{-130}{10} \][/tex]
[tex]\[ y = -13 \][/tex]
4. Substitute the value of [tex]\(y\)[/tex] back into the first equation to find [tex]\(x\)[/tex]
From the first equation, we had:
[tex]\[ x = 3 + y \][/tex]
Substitute [tex]\(y = -13\)[/tex] into this equation:
[tex]\[ x = 3 + (-13) \][/tex]
[tex]\[ x = 3 - 13 \][/tex]
[tex]\[ x = -10 \][/tex]
So, the solution to the system of equations is:
[tex]\[ (x, y) = (-10, -13) \][/tex]
Thus, the correct answer is:
[tex]\[ \text{d. } (-10, -13) \][/tex]
Given:
[tex]\[ \begin{array}{l} x = 3 + y \\ 2x + 8y = -124 \end{array} \][/tex]
1. Substitute the expression for [tex]\(x\)[/tex] from the first equation into the second equation.
The first equation gives us:
[tex]\[ x = 3 + y \][/tex]
Substitute [tex]\(x\)[/tex] in the second equation:
[tex]\[ 2(3 + y) + 8y = -124 \][/tex]
2. Simplify the equation
Distribute the 2 in the equation:
[tex]\[ 6 + 2y + 8y = -124 \][/tex]
Combine like terms:
[tex]\[ 6 + 10y = -124 \][/tex]
3. Isolate the variable [tex]\(y\)[/tex]
Subtract 6 from both sides of the equation:
[tex]\[ 10y = -124 - 6 \][/tex]
Simplify the right-hand side:
[tex]\[ 10y = -130 \][/tex]
Divide both sides by 10:
[tex]\[ y = \frac{-130}{10} \][/tex]
[tex]\[ y = -13 \][/tex]
4. Substitute the value of [tex]\(y\)[/tex] back into the first equation to find [tex]\(x\)[/tex]
From the first equation, we had:
[tex]\[ x = 3 + y \][/tex]
Substitute [tex]\(y = -13\)[/tex] into this equation:
[tex]\[ x = 3 + (-13) \][/tex]
[tex]\[ x = 3 - 13 \][/tex]
[tex]\[ x = -10 \][/tex]
So, the solution to the system of equations is:
[tex]\[ (x, y) = (-10, -13) \][/tex]
Thus, the correct answer is:
[tex]\[ \text{d. } (-10, -13) \][/tex]
We are happy to have you as part of our community. Keep asking, answering, and sharing your insights. Together, we can create a valuable knowledge resource. IDNLearn.com has the solutions you’re looking for. Thanks for visiting, and see you next time for more reliable information.